Strategic Information System Planning at RSUD Berkah Pandeglang Using the EAP (Enterprise Architecture Planning) Method - Anisa Aulia; Nenden Siti Fatonah; Gerry Firmansyah; Agung Mulyono Widodo (CV. Publikasi Indonesia, 2023)
The intense competition in business development requires enterprises to innovate to assist in their business processes. One way to achieve success in innovation is by planning information systems and information technology that can meet business needs and align with current developments, using the Enterprise Architecture Planning (EAP) method. The results of the strategic information system planning include data architecture, application architecture, and network architecture. This research has produced a strategic planning document that can be used by RSUD BERKAH PANDEGLANG. This document contains data architecture, application architecture, and technology architecture.